Boundary Issues in Counseling : Multiple Roles and Responsibilities - Herlihy, Barbara; Corey, Gerald (Alexandria, VA : American Counseling Association, 2015)
'This highly regarded book is essential reading for counselors struggling to find a clear personal position on the range of issues and questions that can arise with multiple relationships. It is also an ideal supplemental text for courses in ethics and professional practice, as well as for practicum and internship seminars to train the next generation of counselors'--Page 4 of cover.
About the authors -- Guest contributors -- Preface -- Boundary issues in perspective -- Sexual dual relationships -- The client's perspective -- Multicultural and social justice perspectives on boundaries -- Issues in counselor education -- Issues in supervision and consultation -- Education and training of group counselors -- Group counseling and couples and family counseling -- Boundary issues in school counseling -- Focus on specialty areas : disaster mental health, private practice -- Focus on specialty areas : rural practice, counseling in the -- Military, working with clients with end-of-life concerns, in-home service provision, and working in forensic settings -- Key themes, questions, and decision making -- References -- Index.
Includes bibliographical references (pages 289-306) and index.
Print version record.
Keywords: Counseling; Counseling -- Moral and ethical aspects; Counseling; Counseling -- Moral and ethical aspects; Electronic books; Electronic books